Ameliorative effects of L-arginine? On heat-induced phase separation of Aristichthys nobilis myosin are associated with the absence of ordered secondary structures of myosin. (March 2021) - Shi, Tong; Xiong, Zhiyu; Liu, Huijie; Jin, Wengang; Mu, Jianlou; Yuan, Li; Sun, Quancai; McClements, David Julian; Gao, Ruichang
Graphical abstract: Highlights: Ordered structures of myosin were converted to disordered structures by L-Arg. The effect was more obvious on rod-rod cross-linking than head-head aggregation. Increasing pH induced by L-Arg increased the electrostatic repulsion of myosin. The cationic L-Arg interacted with anionic groups on the myosin at neutral pH. Heat-induced phase separation of myosin was ameliorated by L-Arg. Abstract: This investigation aimed to study the potential mechanism of L-arginine (L-Arg) on the heat-induced phase separation phenomenon of myosin from the perspective of conformational changes of myosin. L-Arg ameliorated the phase separation of myosin after a two-step heating procedure via suppression of heat-induced aggregation of myosin. The effect of L-Arg on the heating of myosin at high temperatures (75–85 °C) was more pronounced than that in the setting stage (35–45 °C), suggesting that the ameliorative effects of L-Arg on the heat-induced phase separation of myosin are mainly attributed to the inhibition of rod-rod cross-linking between denatured myosin molecules. Additionally, L-Arg without pH modification exhibited an increased ability to suppress the gelation of myosin compared with pH modification, indicating that both pH effects and the particular structure of L-Arg play noticeable roles in the suppression of myosin gelation. Far-UV circular dichroism, intrinsic fluorescence spectroscopy and differential scanning calorimetry demonstrated that L-Arg induced the absence of ordered secondary structures of myosin molecules, especially β-sheets, and thus generated a looser protein structure, which may represent the dominant suppression mechanisms of L-Arg on the heat-induced aggregation of myosin. This work provided support for the use of L-Arg as a food additive, and the results of this study will be attractive to the meat and beverage products.